Environmental remediation of dye effluents using Gracilaria edulis (Marine red alga) mediated green synthesized Ag₂O nanoparticles: Impacts on soil and water quality - G. Visu; N. Muruganantham; P. Anitha; R. Govindharaju; V. Anusuya (Environmental Nanotechnology, Monitoring & Management, 2026)

Anthocyanin accumulation in fruit crops: a multi-layered regulatory network integrating molecular, epigenetic, hormonal and environmental regulation - K. Anchana; S. Saraswathy; C. Rajamanickam; K. Venkatesan; M. Elayarajan; T. Anitha (Molecular Biology Reports, 2026)

Chemometric and computational structure–activity relationship analysis of Ziziphus jujuba and Nephrolepis cordifolia phenolics for antioxidant and antidiabetic potential - Anitha A․; Ponmurugan P․; Arunkumar D․; Vasantha Sakthi S․; Yamuna A․; Jeyapreethi S․ (South African Journal of Botany, 2026)

A comprehensive exploration of MoS2 embedded on coconut waste-derived porous carbon as a new sustainable electrode for advanced symmetric and asymmetric supercapacitor applications - Merin Tomy; Anu Mini Aravind; Xavier Thankappan Suryabai; Anitha Thekkethil Venugopalan; Vimalkumar Thottapurath Vijayan (Next Research, 2026)

Thermal regulation of hydrolysis, oxidation, and structural integrity in palm oil: A biochemical and FTIR–PLSR assessment - Prathap Venkatareddy; Shivashankar Sanganamoni; Suresh Kancherla; Ramachandrudu Kummari; Chirag Maheshwari; Anitha Pedapati; Shaik Sanafrian; Dasarigandla Madhu Babu (Food Chemistry, 2026)

Diversity, Functional Guilds, and Seasonal Variation of Spider Assemblages in Coastal Wetlands of Kerala, India - Anitha Abraham; Mathew M. Joseph (Wetlands, 2026)

Phenolipids: natural origins, synthesis, bioactivity, and functional relevance in food systems - Anupama Anitha Rajamony; Heeba Shakeela; Sobankumar Dasiah Retnabai; Mayumi Ikeda-Imafuku; Tatsuya Fukuta; Kazunori Kadota; Nisha Prakasan (Food Chemistry, 2026)

Association Mapping of Height- and Yield- Related Traits using SSR Markers in Four Oil Palm (E. guineensis Jacq.) Populations - B. Kalyana Babu; G. Ravichandran; K. Suresh; Sandip Shil; Sarika Sahu; Narayana Ruthwek; Mokhamatla Mahesh; P. Anitha; M. Peeyusha Sai (Journal of Plant Growth Regulation, 2026)

Characterization and antioxidant activity of high-methoxyl pectin from red tamarind (Tamarindus indica var. rhodocarpa) - Rajendran Ranjani; Jaganathan Anitha; Asmatanzeem Bepari; Mohd Rasheeduddin Imran; Sayeeda Anjum; Shanmugam Jaiganesh Pradeeba; Meenakshisundram Sangeetha; Sundram Viswanathan; Ramasamy Thangavelu Narendhirakannan (Phytochemistry Letters, 2026)

Advanced green electrochemical pH sensor using phyto-cardamom modified electrode - Sariga; Samriddhi Chatterjee; Mansi Gandhi; Anitha Varghese (Food Chemistry, 2026)

Marker-based standardisation and in-vitro biological activity evaluation of Sudarshanam tablet – an important ayurvedic formulation - Veena K Namboodiri; Tom Cherian; Anitha R; Swathi M; Suresh V Nampoothiri (Natural Product Research, 2026)

Signal and Supply: Phytohormonal networks regulating source sink dynamics and assimilate partitioning - Dharani Jegatheeswaran; Rajamanickam Chinnapalani; Saraswathy Sethurathinam; K. Venkatesan; Vijayasamundeeswari Ayyathurai; Anitha Thiyagarajan; Manjusha Rajan; Vignesh Manoharan (Plant Science, 2026)

Hidden pathways: Detection and quantification of microplastics across treatment stages of pharmaceutical WWTPs - Jey Kumar Pachiyappan; Anitha Marimuthu; Jawahar Natarajan; Praveen Thaggikuppe Krishnamurthy; Thava Palanisami; Gowthamarajan Kuppusamy; P.K. Karuppasamy (Journal of Hazardous Materials, 2026)

Integrated Multi-Omics Reveals Synergistic Hepatotoxicity of Ethanol and PFOS Co-Exposure - Arthur D. Stem; Mohammad Alayyoub; Reza Aalizadeh; Varvara Nikolopoulou; Athina Lisgara; Ava Shvartsman; Mallappa Anitha; Andrew Patterson; Rachel Coble; Blake Rushing; Susan Sumner; Vasilis Vasiliou (Chemico-Biological Interactions, 2026)

Serum human papilloma virus detection following treatment of cervical cancer: prevalence and its correlation with recurrence - Vinotha Thomas; John Dickson Calvin Devadasan; Neenu Oliver John; Jeba Karunya Reddy; Arvind Sathyamurthy; Dhanya Susan Thomas; Gnanadurai John Fletcher; Rajesh Kannangai; Anuradha Chandramohan; Betty Simon; Anitha Thomas; Thomas Samuel Ram; et al. (Cancer Causes & Control, 2026)

Trophic interactions and ecosystem status assessment of a tropical reservoir in the Western Ghats of India using Ecopath - Mohammed Meharoof; Vinod Kumar Yadav; G.B. Sreekanth; Arpita Sharma; Thankam Theresa Paul; V Anitha (Total Environment Advances, 2026)

Differential expression of neurogenesis-relevant genes in the peripheral blood lymphocytes of children with polymicrogyria - Mary Iype; Mithran Omana Surendran; Jesmy James; Aadhira Raghu; Smriti Menon; Arya K. S; Gokul Babu; Rahul Kumminimana; Ayyappan Anitha (Next Research, 2026)

Gymnemagenin-3-O-glucuronide mitigates lipopolysaccharide-induced acute lung inflammation/injury by regulating the NF-κB/MAPK signalling - Aruna Jangam; Sarva Lakshmi Pusarapu; Vaishnavi Kambhampati; Swarna Kumari Gaja; Anitha Rolla; Ankitha Kondepudi; Nagendla Narendra Kumar; Mohana Krishna Reddy Mudiam; Sai Balaji Andugulapati; Anthony Addlagatta (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pollen micromorphology and functional traits as indicators of genetic diversity in Elaeis spp. - M. Neema; S. Suresh; G. Somasundaram; S. G. Silpa; R. P. Premalatha; P. Anitha; G. M. Aswathy (Genetic Resources and Crop Evolution, 2026)

Meta-topolin Stimulates In Vitro Plantlet Generation from Embryonic Shoot Meristem Explants in Coconut (Cocos nucifera) - M. S. Namitha; M. Neema; M. K. Rajesh; M. P. Fathimath Zaeema; Krishna Prakash; K. S. Muralikrishna; Anitha Karun (Agricultural Research, 2026)

Altering scenarios of organic farming pre and post COVID-19 in India: A comprehensive review - Swarna Pragathi Muthana; Anitha Manne; Masha Nur Salsabiela Menhat (Food and Humanity, 2026)

Metformin for knee osteoarthritis in overweight and obese adults: a systematic review and meta-analysis of efficacy, safety, and disease-modifying anti-inflammatory potential - Santenna Chenchula; Krishna Chaitanya Amerneni; R. Padmavathi; K. Anitha; Mohan Krishna Ghanta; Shriraam Karunakaran; Shubham Atal; Sunil Kumar; Pavani Saggurthi; Shoibam Jenifa; K. Mythili Bai; Madhavrao Chavan; et al. (Inflammopharmacology, 2026)

Assessment of the Diurnal Cycle of Sea Surface Temperature from Model Analysis Against Ship-Based Ocean Observations - Imranali M. Momin; S. K. Sahoo; Radharani Sen; Anitha Gera (Journal of the Indian Society of Remote Sensing, 2026)

Unveiling the antibacterial and antioxidant capabilities of Diospyros buxifolia leaf and stem extracts via GC-MS analysis - Praveen Kumar Basivi; Jayaletchumi Raman; Anitha Tippana; Vijay Kakani; Reetesh Kumar; Pasupuleti Visweswara Rao; Chang Woo Kim (Natural Product Research, 2026)

Pyriproxyfen effects on predators of Anopheles arabiensis larvae under semi-field setting: insights into ecosystem safety - Augustino Thabiti Mmbaga; Simoni Twaha Mnzava; Anitha Mutashobya; Esther Gwae Kimaro; Emmanuel W. Kaindoa; Dickson Wilson Lwetoijera (Total Environment Advances, 2026)

Polyphenol-based therapeutics for glioblastoma: validation from In-vitro cell viability assay and integrated onco-omics computational analysis - Yogesh H S; Sadik Shaik; Sibghatullah Muhammad Ali Sangi; Krishna Swaroop; Sreeharsha Nagaraja; Anitha K N; Vipin Kumar Mishra; Santosh Prasad Chaudhary Kurmi; Subrata Nath; Shankar Thapa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Investigations on the Aerosol Type Classification using Machine Learning Techniques over Multiple AERONET Sites in India - M. Anitha; Lakshmi Sutha Kumar (Advances in Space Research, 2026)

Ingenious design and application of ZnAl-LDH/BiOBr Z-scheme heterojunction for effective photocatalytic degradation of tetracycline in aqueous environment: Insight into mechanism and toxicity estimation - R. Janani; M. Kanagalakshmi; S. Gopika Devi; Anitha Pius (Process Safety and Environmental Protection, 2026)

Smoke-derived microplastics of polypropylene In Vitro proliferative impact on human lung adenocarcinoma cells: Physicochemical analysis and biological evaluation - Nivedita Jha; Angshita Das; Megha Prasanth; S. Daisy Precilla; R. Sivachandran; Rajaneesh Anupam; T.S. Anitha (Environmental Toxicology and Pharmacology, 2026)

Toxicity and antiproliferative activity assessment of a novel compound Zr I isolated from Zingiber roseum Rosc - Swarnalatha P.; Deepika Divya K.; Anjali Jha; Anitha M.; S. P. D. Ponamgi; Seema Kumari; Sujatha Peela (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluation of the anti-inflammatory and wound healing potential of Ayapana protein extracted from fresh leaves of Ayapana triplinervis Vahl - In vitro - Anitha P; Balasubramanian Murugesan (Next Research, 2025)

Sex-based differences in rainbow trout innate immunity: in vivo and in vitro gene expression - Yubing Chen; Anitha Bhat; Olivia Hou-Ling Dixon; Jesús Luis Betancourt; Tania Rodriguez-Ramos; Brian Dixon (Fish & Shellfish Immunology, 2025)

Neuroprotective capacity of Celastrus paniculatus on rotenone-induced parkinsonism in zebrafish model - Nivedita Manoharan; Dheepthi Jayamurali; Anitha Sridhar; Sathya Narayanan Govindarajulu (Molecular Biology Reports, 2025)

Land Use Land Cover Change Detection for Fish Culture Area Mapping in the Peechi Reservoir - Mohammed Meharoof; Vinod Kumar Yadav; Arpita Sharma; Shekhar Nath Ojha; V. Anitha; Thankam Theresa Paul (Journal of the Indian Society of Remote Sensing, 2025)

Interplay of flux-controlled memristive synapse and Josephson junction properties in modified Morris–Lecar neuron dynamics - Mohanasubha Ramasamy; S. Senthamizh Selvi; Anitha Karthikeyan; S. Dinesh Vijay; Karthikeyan Rajagopal (Cognitive Neurodynamics, 2025)

Foliar formulation from shrimp head silage and chitosan oligosaccharide for improved growth and yield of cowpea (Vigna unguiculata L. Walp.) - Angel Maria Selassy; Sarasan Sabu; Abhilash Sasidharan; Sarala Anitha (Organic Agriculture, 2025)

Bioprospecting of exopolysaccharides from the endophytic fungi Epicoccum sorghinum AMFS4, for its structure, composition, bioactivities and application in seed priming - Santhanalakshmi Balasubramaniam; Anitha Sakthivel; Kaviraj Ramesh; Chithra Manisseeri; Sivanandhan Ganeshan; Mayavan Subramani; Kapildev Gnanajothi (Natural Product Research, 2025)

Bias correction of MODIS retrieved Aerosol Optical Depth using Machine Learning and Deep Learning Techniques - M. Anitha; Lakshmi Sutha Kumar (International Journal of Remote Sensing, 2025)

Unravelling resistance to sunflower necrosis disease: a molecular diagnostic and physiological trait-based approach to identify TSV-resilient germplasm - Chaitra Govinakovi Veereshappa; Parameswari Balasubramaniam; Pranusha Pulivendula; Sakhare Akshay Sureshrao; Anitha Kodaru; Bhaskar Bajaru; Lakshman Saravanan; Celia Chalam Vasimella; Gyanendra Pratap Singh (Journal of Plant Pathology, 2025)

Photocatalytic hydrogel impregnated CoMgAl layered double oxide and biochar for visible light driven degradation of agrochemical contaminants in real water matrices - M. Kanagalakshmi; Nanthan kumar T.R.; R. Janani; Anitha Pius (Chemical Engineering Journal, 2025)

Visible-light driven photocatalytic degradation of triphenylmethane and azo dyes using a graphene oxide reinforced pectin hydrogel - M. Kanagalakshmi; S. Subasini; Anitha Pius (Carbohydrate Polymers, 2025)

Resveratrol mitigates activated astrocytes and microglia preventing Alzheimer’s Disease (AD) progression and facilitates neuronal communication in Amyloid-β25–35 induced rat model for AD: A special emphasis on non-neuronal involvement in AD pathophysiology - Kumar Surya; Anitha Rathinam; Meher Nisha Abubakkar; Kesavan Swaminathan Jayachandran; Mahesh Kandasamy; Muthuswamy Anusuyadevi (Psychopharmacology, 2025)

Performance Assessment of MODIS Dark Target and Deep Blue Aerosol Retrieval Algorithms Using AERONET Observations: A Case Study over Jaipur, Karunya University, and Broader Indian Regions - M. Anitha; Lakshmi Sutha Kumar (Environmental Monitoring and Assessment, 2025)

Determining the efficacy of phytoconstituents of Ficus religiosa L. against dermatophytes through invitro and insilico approaches - A. Anitha; P. Ponmurugan; V. Hemamalini; D. Arunkumar (In Silico Pharmacology, 2025)

Solvatochromism provoked multi-emissive polyethylenimine assimilated carbon dots for fluorescence sensing and adsorptive removal of copper and bismuth ions in aqua regions - Nawas Sherif Z; Anitha K (Environmental Research, 2025)

Age-Related Macular Degeneration: Therapeutic Strategies Based on Stem Cells - Isai Mathivanan; Enzmann Volker; Keerthana Thyagarajan; Anitha Thirugnanasambantham Sivasubramanian; Kamaraj Raju; Annadurai Thangaraj (Stem Cell Reviews and Reports, 2025)

Transforming waste management: leveraging recycletransformernet for effective recycling strategies - A. Devi; Amirtha Saravanan; R. Reeta; V. P. Anitha (Clean Technologies and Environmental Policy, 2025)

Nutritional profile of probiotic-enriched potato yogurt as a plant-based alternative to dairy yogurt - S. Anitha; A. Manivannan (Next Research, 2025)

Microbially-driven nitrous oxide transformations and fluxes in organic-poor sediments from a tropical lagoon - Tanisha Nag; Damodara Rao Valavala; Anitha Gera; Sanitha K. Sivadas; M. Govindaraju; M.V. Ramana Murthy (Marine Environmental Research, 2025)

Surface modified Cobalt Oxide Nanostructures for hydrogen generation from catalytic dissociation of NaBH4 - Anitha Abraham; Suraj Gupta; Rupali Patel; Nainesh Patel; Rohan Fernandes (Fuel, 2025)

Optimization of nutritional properties of black soldier fly larvae via supplementation using oil cakes, husk, Bran and unhatched eggs: applications for Waste-to-Feed conversion and sustain feed enhancement - D. Saicharan; V. Anitha; G. Anitha; A. Kalaisekhar; Bhojendra Patel (Environment, Development and Sustainability, 2025)

Optimization of potato yogurt using response surface methodology: Exploring a non-dairy substitute - S Anitha; A Manivannan (Next Research, 2025)

Silver decorated copper coordination polymer for the electroreduction of CO2 to hydrocarbon liquid fuels - Ann Mariella Babu; Sobin Mathew; Anitha Varghese (Journal of Environmental Chemical Engineering, 2025)

Development of MOF and Cleome Gynandra infused guar gum film: A high- performance antibacterial and antioxidant packaging solution for fruits shelf life extension - P. Ananthi; K. Hemkumar; Anitha Pius (Food Packaging and Shelf Life, 2025)

One step facile green synthesis of ZnFe2O4-ZnO Nanocomposite: Efficient photocatalytic activity towards organic dyes under visible light and photoluminescence applications - E.Vinay Kumar; R. Harini; Anitha; B.E. Kumara Swamy; G. Nagaraju (Environmental Nanotechnology, Monitoring & Management, 2025)

Neuroprotective Potential of Chromium-D-Phenylalanine: Insights from Molecular Docking, Dynamics and Rotenone-Induced Parkinsonism in Rats - K. N. Anitha; Mohammed Mutahir; Shivsharan B. Dhadde; B. S. Gowrishankar; Vivek Chandramohan (Biological Trace Element Research, 2025)

Reactive oxygen species responsive dextran-thioketal conjugate nanocarriers for the delivery of hydrophilic payloads - Sourav Nayak; Nuran Caz; Elien Derveaux; Sander Smeets; Tom Cardeynaels; Esther Wolfs; Peter Adriaensens; Wouter Maes; Anitha Ethirajan (Carbohydrate Polymers, 2025)

Short-Term Response of Mandous Severe Cyclone on Coastal Water Quality Along Southwestern Bay of Bengal, India - Subhasis Pradhan; P. Senthilkumar; Umakanta Pradhan; Subrat Naik; Rabindra Kumar Sahoo; Anitha Gera; Uma Sankar Panda; Pravakar Mishra; M. V. Ramana Murthy; P. Vipin Babu (Pure and Applied Geophysics, 2025)

Phytochemical compounds for treating hyperuricemia associated with gout: a systematic review - Santenna Chenchula; Mohan Krishna Ghanta; Munirah Alhammadi; Arifullah Mohammed; Kuttiappan Anitha; Poojith Nuthalapati; Ganji Seeta Rama Raju; Yun Suk Huh; LVKS Bhaskar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

Amelioration of amyloid-beta (25–35)-induced neurotoxicity by Eclipta alba (L.) Hassk.: evidence from behavioural and oxidative analyses - Abir Biswas; Meher Nisha Abubakkar; Anitha Rathinam; Kumar Surya; Giri Prashanth; Kesavan Swaminathan Jayachandran; Muthuswamy Anusuyadevi (Neurophysiology, 2025)

From cognition to economic valuation of cultural ecosystem services – An evidence from Parambikulam tiger reserve, Kerala - Divya Soman; V. Anitha; Syam Viswanath; M. Sreeraj (Journal for Nature Conservation, 2025)

Evolving dynamics of municipal solid waste management in India: a comprehensive review of status, challenges, opportunities and policy innovations - Anitha Rengerla; Parthiban Angamuthu (Waste Disposal & Sustainable Energy, 2025)

Exploring rice genotypes for nitrogen use efficiency under different nitrogen regimes - Sritharan Natarajan; Krishna Surendar Karuppasamy; Anitha Ramasamy; Tamilselvi Chellamuthu; Nithila Sadasivam; Boomiraj Kovilpillai; Senthil Kumar Govindan; Ravichandran Veerasamy; Raveendran Muthurajan (Plant Physiology Reports, 2025)

An investigation on the mechanical and microstructural properties of pigeon pea stalk ash concrete: an approach towards environmental sustainability - Anitha Krishnan; Senthil Selvan Subramanian (Environmental Science and Pollution Research, 2025)

A Spectroscopic Investigation into the Stability of Carbon Dots Derived from Polyethylene Glycol - K. R. Athulya; Arathy Chandran; Tirupati Rao Bantu; Anitha C. Kumar (Journal of Fluorescence, 2025)

Trace Element Chromium-D-Phenylalanine Complex: Anti-Inflammatory and Antioxidant Insights from In Vivo and In Silico Studies - K. N. Anitha; M. C. Darshan; Shivsharan B. Dhadde (Biological Trace Element Research, 2025)

Recent Insights into the Neurobiology of Alzheimer’s Disease and Advanced Treatment Strategies - Anitha K; Mandeep Kumar Singh; Komal Kohat; Sri Varshini T; Santenna Chenchula; Padmavathi R; Lakshmi Sahitya Amerneni; Vishnu Vardhan K; Mythili Bai K; Madhav Rao Chavan; Shvetank Bhatt (Molecular Neurobiology, 2025)

Understanding the mechanisms of long noncoding RNAs in response to bacterial blight in rice - Selva Babu Selvamani; Saranya Nallusamy; Vinothini Kamalanathan; Anitha Ravichandran; Ramanipriya Singaravelu; Upasna Selvapandian; Varanavasiappan Shanmugam; Nakkeeran Sevugapperumal; Ramalingam Jegadeesan; Gnanam Ramasamy; Raveendran Muthurajan; Senthil Natesan (Physiological and Molecular Plant Pathology, 2025)

Development of reverse transcription recombinase polymerase amplification assay for rapid diagnostics of Peanut mottle virus - B. Parameswari; P. Anbazhagan; A. Rajashree; G. V. Chaitra; Kavi Sidharthan; S. K. Mangrauthia; Faisal Yousuf; K. Anitha; Y. Prasanthi; B. Bhaskar; V. Celia Chalam; G. P. Singh (Physiology and Molecular Biology of Plants, 2025)

Advancing aquaculture: fuzzy logic-based water quality monitoring and maintenance system for precision aquaculture - Sudheer Kumar Nagothu; Pudota Bindu Sri; G. Anitha; Shweta Vincent; Om Prakash Kumar (Aquaculture International, 2025)
Aquaculture plays a vital role in global food production, and maintaining optimal water quality is essential for the health and growth of aquatic species. This research addresses the need for an efficient, adaptive solution by introducing an innovative water quality monitoring and maintenance system for aquaculture ponds. Unlike conventional systems, our approach uniquely integrates fuzzy logic with IoT technologies to optimise the precision and adaptability of pond management. The system stands out with its continuous monitoring of critical parameters such as temperature, pH, dissolved oxygen (DO), weather conditions and salinity and its ability to autonomously adjust operational controls, such as aerators and water pumps, based on dynamic environmental changes. This ensures ideal water conditions without manual intervention, providing a reliable and effective solution for aquaculture pond management. This work’s novelty lies in applying fuzzy Logic to handle the complexity and variability of aquaculture environments, allowing for nuanced control decisions that improve water quality management. The system’s efficiency was demonstrated through a 72-h operational test, where it maintained optimal DO and salinity levels, showcasing its reliability and effectiveness in real-world conditions. The fuzzy logic model has demonstrated a commendable accuracy rate of 98%. These results validate the system’s performance and underscore its practical benefits, meeting the demands of aquaculture production and significantly enhancing operational efficiency by enabling remote monitoring and rapid issue identification. This research contributes a robust technological solution for aquafarmers, offering a promising advancement in aquaculture management by improving productivity and ensuring the health and growth of aquatic species.

Exploring the microbial diversity of zoanthids: a gateway to novel marine natural products and biotechnological breakthroughs - Antony Anitha; Vattiringal Jayadradhan Rejish Kumar; Janardhanan Choweth Anjana; Meethal Parambath Prabhakaran; Prasannan Geetha Preena (Biologia, 2024)

Spectroscopic Investigation of Hydrogels Formed from Phenylalanine - Arathy Chandran; K. R. Athulya; Anitha C. Kumar (Journal of Fluorescence, 2024)

The synergistic anti-Warburg efficacy of temozolomide, metformin and epigallocatechin gallate in glioblastoma - Shreyas S. Kuduvalli; Daisy Precilla Senthilathiban; Indrani Biswas; Justin S. Antony; Madhu Subramani; T.S. Anitha (Toxicology and Applied Pharmacology, 2024)

Cymodocea serrulata as sources of biopesticides: A novel approach managing crop insects in Solanum melongena L. (Solanales: Solanaceae) - Mythili Ravichandran; Rani Elavarasan Anitha; B.T. Sureshkumar; T.T. Ajith Kumar; Salim Manoharadas; Naushad Ahmad; Mohammad Rizwan Khan; R. Dineshkumar (Sustainable Chemistry and Pharmacy, 2024)

Impact of shallow hydrothermal vent waters on monsoonal copepod distribution and abundance around active volcanic island off northeast Taiwan, West Pacific - Anitha Mary Davidson; Li-Chun Tseng; Yan-Guo Wang; Jiang-Shiou Hwang (Science of The Total Environment, 2024)

Exploring the potential therapeutic benefits of 7-methoxy coumarin for neuropathy pain: an in vivo, in vitro, and in silico approach - Binoy Varghese Cheriyan; Jaikumar Shanmugasundaram; Prakash Ramakrishnan; Kavitha Ramasamy; R. Karthikeyan; Sowmyalakshmi Venkataraman; Anitha Roy; Parameswari Royapuram Parthasarathy (Molecular Biology Reports, 2024)

Investigation on the regular and chaotic dynamics of a ring network of five inertial Hopfield neural network: theoretical, analog and microcontroller simulation - Jean Baptiste Koinfo; Sridevi Sriram; Kengne Jacques; Anitha Karthikeyan (Cognitive Neurodynamics, 2024)

Efficacious sensing and elimination of iron ions from aqueous medium by polyethylenimine functionalized carbon dot - Z. Nawas Sherif; K. Anitha (Journal of Environmental Chemical Engineering, 2024)

Alkaloid-based modulators of the PI3K/Akt/mTOR pathway for cancer therapy: Understandings from pharmacological point of view - Fatima Zohra Mokhfi; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Jeetendra Kumar Gupta; Bhaskar Vallamkonda; Anitha Balakrishnan; Manjula Challa; Jyoti Singh; P. Dharani Prasad; Syed Salman Ali; et al. (Chemico-Biological Interactions, 2024)

Correction to: Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Kavitha Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)

Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Joseph Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)
Dengue is an emerging, mosquito-borne viral disease of international public health concern. Dengue is endemic in more than 100 countries across the world. However, there are no clinically approved antivirals for its cure. Drug repurposing proves to be an efficient alternative to conventional drug discovery approaches in this regard, as approved drugs with an established safety profile are tested for new indications, which circumvents several time-consuming experiments. In the present study, eight approved RNA-dependent RNA polymerase inhibitors of Hepatitis C virus were virtually screened against the Dengue virus polymerase protein, and their antiviral activity was assessed in vitro. Schrödinger software was used for in silico screening, where the compounds were passed through several hierarchical filters. Among the eight compounds, dasabuvir was finally selected for in vitro cytotoxicity and antiviral screening. Cytotoxicity profiling of dasabuvir in Vero cells revealed changes in cellular morphology, cell aggregation, and detachment at 50 μM. Based on these results, four noncytotoxic concentrations of dasabuvir (0.1, 0.25, 0.5, and 1 µM) were selected for antiviral screening against DENV-2 under three experimental conditions: pre-infection, co-infection, and post-infection treatment, by plaque reduction assay. Viral plaques were reduced significantly ( p < 0.05) in the co-infection and post-infection treatment regimens; however, no reduction was observed in the pretreatment group. This indicated a possible interference of dasabuvir with NS5 RdRp, as seen from in silico interaction studies, translating into a reduction in virus plaques. Such studies reiterate the usefulness of drug repurposing as a viable strategy in antiviral drug discovery. Graphical Abstract In this drug repurposing study, dasabuvir, a known anti-hepatitis C drug, was selected through virtual screening and assessed for its anti-dengue activity.

Microproteins unveiling new dimensions in cancer - S. Daisy Precilla; Indrani Biswas; T. S. Anitha; B. Agieshkumar (Functional & Integrative Genomics, 2024)

Unraveling the dynamics of a flux coupled Chialvo neurons and the existence of extreme events - Sathiyadevi Kanagaraj; Premraj Durairaj; Anitha Karthikeyan; Karthikeyan Rajagopal (Cognitive Neurodynamics, 2024)

Leveraging experimental and computational tools for advancing carbon capture adsorbents research - Niranjan Ramasamy; Anitha Jegadeeshwari Lakshmana Peru Raj; Vedha Varshini Akula; Kavitha Nagarasampatti Palani (Environmental Science and Pollution Research, 2024)

Ethnopharmacological potential of Anisomeles malabarica : a systematic review on traditional uses and bioactive compounds - Balasubramaniam Santhanalakshmi; Ganeshan Sivanandhan; Sampath Manojkumar; Sakthivel Anitha; Gogoi Sharmistha; Natesan Selvaraj; Gnanajothi Kapildev (Plant Biosystems, 2024)

Corrigendum to “Microwave-Assisted dry reforming of toluene as a model tar compound using low-cost iron catalyst for syngas clean-up” [Fuel 370 (2024) 131843] - Xinwei Bai; Ashraf Abedin; Anitha Shankara Linge Gowda; Victor Abdelsayed; Pranjali Muley (Fuel, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Mortality of mesozooplankton in an acidified ocean: Investigating the impact of shallow hydrothermal vents across multiple monsoonal periods - Anitha Mary Davidson; Li-Chun Tseng; Yan-Guo Wang; Jiang-Shiou Hwang (Marine Pollution Bulletin, 2024)

Cellulose acetate based-membrane supported by metal-organic frameworks for the removal of diclofenac and ciprofloxacin from polluted water - Ananthi P; Hemkumar K; Manikandan S; Anitha Pius (Groundwater for Sustainable Development, 2024)

Microwave-Assisted dry reforming of toluene as a model tar compound using low-cost iron catalyst for syngas clean-up - Xinwei Bai; Ashraf Abedin; Anitha Shankara Linge Gowda; Victor Abdelsayed; Pranjali Muley (Fuel, 2024)

Does agroforestry contribute to household food security? A micro-perspective from southern Rwanda - Jules Ngango; Edouard Musabanganji; Aristide Maniriho; Ferdinand Nkikabahizi; Anitha Mukamuhire; John N. Ng'ombe (Forest Policy and Economics, 2024)

Identification of sources of resistance and comparative metabolomic profiling of resistant and susceptible chilli germplasm to Meloidogyne incognita Race 1 - Prasanna Holajjer; T. P. Ahammed Shabeer; M. K. Mahatma; Z. Khan; S. R. Pandravada; N. Sivaraj; Anitha Kodaru; Anita Pardeshi (Australasian Plant Pathology, 2024)

Enhancement of grain yield in rice under combined drought and high-temperature stress conditions by maintaining photosynthesis through antioxidant enzyme activities by melatonin - Arun Kumar Kathirvel; Kalarani M. Karuppasami; Vijayalakshmi Dhashnamurthi; Geethalakshmi Vellingiri; Raveendran Muthurajan; Anandhi Venugopal; Anitha Kuppusamy; Senthil Alagarsamy (Plant Physiology Reports, 2024)

Butea monosperma aided green synthesis of α-MoO3 nanoparticles: Biosensing and photocatalytic activity towards hazardous dyes and rangoli colorants - E. Vinay Kumar; T.L. Soundarya; B.E. Kumara Swamy; Anitha; G. Nagaraju (Environmental Nanotechnology, Monitoring & Management, 2024)

Improved photocatalytic degradation of organic pollutants using green synthesized ZnO and Ni@ZnO NPs for environmental applications - N.S. Mohan; S. Bhuvaneswari; R. Anitha; V. Vijayalakshmi (Environmental Nanotechnology, Monitoring & Management, 2024)

Dissipation and evaluation of different treatments on the residues of different insecticides in/on cauliflower curd - Anitha Vijay; Ravi L. Kalasariya; Paresh H. Rathod; Suchi Chawla; Rajesh R. Acharya (Food Additives & Contaminants: Part A, 2024)

Imperfect chimera and synchronization in a hybrid adaptive conductance based exponential integrate and fire neuron model - Sathiyadevi Kanagaraj; Irene Moroz; Premraj Durairaj; Anitha Karthikeyan; Karthikeyan Rajagopal (Cognitive Neurodynamics, 2024)

Effect of novel combination processing technologies on extraction and quality of rice bran oil - Nikitha Modupalli; Anitha Krisshnan; Sunil C. K.; Chidanand D. V.; Venkatachalapathy Natarajan; Anastasios Koidis; Ashish Rawson (Critical Reviews in Food Science and Nutrition, 2024)

Impacts of combined drought and high-temperature stress on growth, physiology, and yield of crops - K. A. Mumithra Kamatchi; K. Anitha; K. Arun Kumar; A. Senthil; M. K. Kalarani; M. Djanaguiraman (Plant Physiology Reports, 2024)

Development of 1-phenyl-3-(4-(pyridin-4-ylmethyl)phenyl)urea derivatives as robust corrosion inhibitors for mild steel in 1 M HCl environment: Insight from ,molecular, experimental, and microscopic-scale modelling approaches - Arumugam Ramachandran; Panneerselvam Anitha; Sadhasivam Gnanavel; Subramania Angaiah (Journal of Environmental Chemical Engineering, 2024)

Investigation of pre-treatment techniques on spent substrate of Pleurotus ostreatus for enhanced biobutanol production using Clostridium acetobutylicum MTCC 11274 - Ashwin Raj Suresh; Anitha Shalini Alphonse mani; Kirupa Sankar Muthuvelu (Bioresource Technology, 2024)

An investigation on antidiabetic competence of Ferula assafoetida mediated AgNPs on diabetic (STZ) induced albino rats - Saranyadevi Subramaniam; Anitha Roy; K.E. Vivekanandan; A. Asrar Ahamed; C. Bharathiraja; Suresh Kumarasamy; Rathinam Raja; Mohamad S.AlSalhi; Mathiyazhagan Narayanan (Biocatalysis and Agricultural Biotechnology, 2024)

An Analysis of Atmospheric Aerosol Characteristics Using Remote Sensing Data in the Indian Region - M. Anitha; Lakshmi Sutha Kumar (Pure and Applied Geophysics, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Dual ion specific electrochemical sensor using aminothiazole-engineered carbon quantum dots - P. Keerthana; Ashlay George; M. Bharath; Munmun Ghosh; Anitha Varghese (Chemical Engineering Journal, 2024)

Synthesis of sulfated alginate from its tributylammonium salt: Comparing the sulfating agents H2SO4-DCC and SO3·py - Alexandra L. Mutch; Vito Ferro; Anitha A; Lisbeth Grøndahl (Carbohydrate Polymers, 2024)

Dynamics, synchronization and traveling wave patterns of flux coupled network of Chay neurons - Dianavinnarasi Joseph; Rakshanaa Kumar; Anitha Karthikeyan; Karthikeyan Rajagopal (BioSystems, 2024)

Bioprospecting of Novel and Industrially Appropriate Enzymes: a Review - Anitha Thulasisingh; Krithika Ananthakrishnan; Avendhika Raja; Sathishkumar Kannaiyan (Water, Air, & Soil Pollution, 2024)

Composition and source based aerosol classification using machine learning algorithms - S.M Annapurna; M. Anitha; Lakshmi Sutha Kumar (Advances in Space Research, 2024)

Detection and removal of cadmium ion by a neoteric polyethylenimine carbon dots @ lanthanum orthoferrite nanocomposite - Nawas Sherif Z; Anitha K (Journal of Water Process Engineering, 2023)

The use of ultrasonication in producing potato-based milk, and to determine its proximate composition - Anitha. S; Manivannan. A (Food and Humanity, 2023)

Antioxidant activity, total phenolic content, and total flavonoid content of potato milk – A novel functional beverage developed as an alternative to cow milk - S. Anitha; A. Manivannan (Food and Humanity, 2023)

Processing of functional yogurt-like product from potato milk supplemented with probiotic bacteria and evaluation of its proximate composition - Anitha S; Manivannan A (Food and Humanity, 2023)

Ultrasound-assisted preparation of potato milk and optimizing the formulation via response surface methodology - Anitha S; Manivannan A (Food and Humanity, 2023)

Nutritional evaluation of potato milk produced by ultrasonication–A functional alternative for bovine milk - Anitha S; Manivannan A (Food and Humanity, 2023)

Development of nanorods-like Fe2O3 @ functionalized carboxy methyl cellulose – SiO2 composite for the removal of pesticides and antibiotics - E. Jackcina Stobel Christy; N. Suba Lekha; K. Hemkumar; Anitha Pius (Environmental Nanotechnology, Monitoring & Management, 2023)

Synchronization Studies of Hindmarsh–Rose Neuron Networks: Unraveling the Influence of connection induced memristive synapse - Dianavinnarasi Joseph; Raja Ramachandran; Anitha Karthikeyan; Karthikeyan Rajagopal (BioSystems, 2023)

Challenges, limitations, and applications of nanofluids in solar thermal collectors—a comprehensive review - Lukman Ahmed Omeiza; Muhammad Abid; Yathavan Subramanian; Anitha Dhanasekaran; Saifullah Abu Bakar; Abul Kalam Azad (Environmental Science and Pollution Research, 2023)

Targeting inflammatory signaling in obsessive compulsive disorder: a promising approach - Shvetank Bhatt; Kuttiappan Anitha; Dinesh Kumar Chellappan; Dhrubojyoti Mukherjee; Satish Shilpi; Ashish Suttee; Gaurav Gupta; Thakur Gurjeet Singh; Kamal Dua (Metabolic Brain Disease, 2023)

Drug Dissolution in Oral Drug Absorption: Workshop Report - Kimberly Raines; Payal Agarwal; Patrick Augustijns; Alaadin Alayoubi; Lucas Attia; Annette Bauer-Brandl; Martin Brandl; Parnali Chatterjee; Hansong Chen; Yuly Chiang Yu; Carrie Coutant; Ana Luisa Coutinho; et al. (The AAPS Journal, 2023)
The in-person workshop “Drug Dissolution in Oral Drug Absorption” was held on May 23–24, 2023, in Baltimore, MD, USA. The workshop was organized into lectures and breakout sessions. Three common topics that were re-visited by various lecturers were amorphous solid dispersions (ASDs), dissolution/permeation interplay, and in vitro methods to predict in vivo biopharmaceutics performance and risk. Topics that repeatedly surfaced across breakout sessions were the following: (1) meaning and assessment of “dissolved drug,” particularly of poorly water soluble drug in colloidal environments ( e.g. , fed conditions, ASDs); (2) potential limitations of a test that employs sink conditions for a poorly water soluble drug; (3) non-compendial methods ( e.g. , two-stage or multi-stage method, dissolution/permeation methods); (4) non-compendial conditions ( e.g. , apex vessels, non-sink conditions); and (5) potential benefit of having both a quality control method for batch release and a biopredictive/biorelevant method for biowaiver or bridging scenarios. An identified obstacle to non-compendial methods is the uncertainty of global regulatory acceptance of such methods.

Silicon nanoparticles (SiNPs): Challenges and perspectives for sustainable agriculture - M. Yuvaraj; R. Sathya Priya; N. Jagathjothi; M. Saranya; N. Suganthi; R. Sharmila; Jaiby Cyriac; R. Anitha; K.S. Subramanian (Physiological and Molecular Plant Pathology, 2023)

Modulation of PPAR-γ, SREBP-1c and inflammatory mediators by luteolin ameliorates β-cell dysfunction and renal damage in a rat model of type-2 diabetes mellitus - Syed Ilyas Shehnaz; Anitha Roy; Rajagopalan Vijayaraghavan; Senthilkumar Sivanesan; Natesan Pazhanivel (Molecular Biology Reports, 2023)

One Pot Hydrothermal Synthesis and Application of Bright-yellow-emissive Carbon Quantum Dots in Hg2+ Detection - Ann Mary Chakkola Jaison; Devipriya Vasudevan; Keerthana Ponmudi; Ashlay George; Anitha Varghese (Journal of Fluorescence, 2023)

Vegetable grafting: a green technique to combat biotic and abiotic stresses - A. Remzeena; P. Anitha (Vegetos, 2023)

Public spending and natural resources development: A way toward green economic growth in China - Yating Guo; Anitha Rosland; Suryati Ishak; Mohammad Khair Afham Muhammad Senan (Resources Policy, 2023)

Collective dynamics of a coupled Hindmarsh–Rose neurons with locally active memristor - Sathiyadevi Kanagaraj; Premraj Durairaj; Sivaperumal Sampath; Anitha Karthikeyan; Karthikeyan Rajagopal (BioSystems, 2023)

Fluoride Binding Potential of Selected Phytochemicals: A Pilot Study - Harsheema Ottappilakkil; Anitha Ottoor; Suryaa Manoharan; Murugesapandian Balasubramanian; Ekambaram Perumal (Environmental Science and Pollution Research, 2023)

Peach (Prunus persica (L.) Batsch) seeds and kernels as potential plant-based functional food ingredients: A review of bioactive compounds and health-promoting activities - Neeraj Kumari; Radha; Manoj Kumar; Sunil Puri; Baohong Zhang; Nadeem Rais; Ashok Pundir; Deepak Chandran; Priya Raman; Sangram Dhumal; Abhijit Dey; Marisennayya Senapathy; et al. (Food Bioscience, 2023)

Complex dynamics in a fractional order nephron pressure and flow regulation model - Karthikeyan Rajagopal; Anitha Karthikeyan (BioSystems, 2023)

Probiotic incorporation into edible packaging: A recent trend in food packaging - Vishnupriya Subramaniyan; D. Priscilla Mercy Anitha; Periyar Selvam Sellamuthu; Sadiku Emmanuel Rotimi (Biocatalysis and Agricultural Biotechnology, 2023)

A Simplified Isothermal Recombinase Polymerase Amplification Assay for Detection of Sugarcane bacilliform virus Infection - B. Parameswari; S. K. Sharma; L. Karthikaiselvi; Baby Wangkhem; K. Nithya; R. Viswanathan; G. P. Rao; V. Celia Chalam; K. Anitha (Sugar Tech, 2023)

The threshold analysis of economic growth, FDI and trade on environment pollution in China using provincial panel data - Caihong Tang; Anitha Rosland; Rizwana Yasmeen; Yunfei Long (Environment, Development and Sustainability, 2023)

Study of plant-based cosmeceuticals and skin care - Anitha Selwyn; Sujatha Govindaraj (South African Journal of Botany, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Water depth effect on energy, exergy losses, and exergy efficiency of solar still with wick materials: an experimental research - Parimala Vellivel; Savithiri Vembu; Anitha Gunasekaran; Sivakumar Vaithilingam (Environmental Science and Pollution Research, 2023)

Targeting Redundant ROBO1 and SDF-1 Pathways Prevents Adult Hemangioblast Derived-EPC and CEC Activity Effectively Blocking Tumor Neovascularization - Anitha K. Shenoy; Liya Pi; Alexander P. Ligocki; Koji Hosaka; Christopher R. Cogle; Edward W. Scott (Stem Cell Reviews and Reports, 2023)

A ratiometric fluorescent sensor based on dual-emissive carbon dot for the selective detection of Cd2+ - P. Keerthana; Avijit Kumar Das; M. Bharath; Munmun Ghosh; Anitha Varghese (Journal of Environmental Chemical Engineering, 2023)

Assessment of diversity in anti-nutrient profile, resistant starch, minerals and carbohydrate components in different ricebean (Vigna umbellata) accessions - Paras Sharma; Giridhar Goudar; Anil Kumar Chandragiri; R. Ananthan; K. Subhash; Anitha Chauhan; T. Longvah; Mohar Singh; Rakesh Bhardwaj; Swarup Kumar Parida; Amit Kumar Singh; Gayacharan; et al. (Food Chemistry, 2023)

Design optimisation and fabrication of amino acid based molecularly imprinted sensor for the selective determination of food additive tartrazine - Ashlay George; Anila Rose Cherian; Biju Jacob; Anitha Varghese; Thandavarayan Maiyalagan (Food Chemistry, 2023)

Coupled physical-biogeochemical simulations of upwelling, ecological response to fresh water - Anitha Gera; R Gayathri; P Ezhilarasan; V Ranga Rao; M V Ramana Murthy (Ecological Modelling, 2023)

Freeze v/s air-dried alginate-pectin gel beads modified with sodium dodecyl sulphate for enhanced removal of copper ions - Utkarsh Upadhyay; Sadamanti Sireesha; Sarthak Gupta; I. Sreedhar; K.L. Anitha (Carbohydrate Polymers, 2023)

The emergence of human metapneumovirus G gene duplication in hospitalized patients with respiratory tract infection, India, 2016–2018 - Preetiparna Parida; Sudheesh N; Sanjay E.R; Anitha Jagadesh; Srilatha Marate; Arunkumar Govindakaranavar (Molecular Biology Reports, 2023)
Background Human metapneumovirus (HMPV) belongs to the family Pneumoviridae. It is one of the emerging respiratory viruses causing both upper and lower respiratory tract illnesses. HMPV has two genotypes: A and B. These genotypes are classified into lineage A1, A2, B1 and B2. Lineage-A2 is further classified as A2a, A2b and A2c. Similarly, B2 is classified as B2a and B2b. Studies have shown the circulation of A2b, B1 and B2 lineages in India. However, a limited amount of data is available on the current circulating genotypes of HMPV in India. Methods Throat swab samples positive for HMPV by real-time RT- PCR, archived at Manipal Institute of Virology as a part of a hospital-based acute febrile illness surveillance study, was used from April 2016 to August 2018 by purposive sampling method. We performed the conventional reverse transcriptase-polymerase chain reaction for twenty samples targeting the G gene and then subjected them to sequencing. Phylogenetic analysis was done using MEGA X software by the Maximum Likelihood method. Results All the twenty sequences belonged to the A2c subgroup. Phylogenetic analysis showed that strains from the study have genetic relation with circulating strains in Japan, China and Croatia. Seven out of the twenty sequences showed 180-nucleotide duplication and eleven sequences showed 111-nucleotide duplication. Two sequences did not show any duplications. Conclusion In the current study, we report that A2c is the sub-lineage in India from April 2016 to August 2018. This study is the first retrospective study reporting the circulation of the A2c sub-lineage among adults in India with 180- and 111-nucleotide duplications in the G gene of human metapneumovirus.

A discrete Huber-Braun neuron model: from nodal properties to network performance - Shaobo He; Karthikeyan Rajagopal; Anitha Karthikeyan; Ashokkumar Srinivasan (Cognitive Neurodynamics, 2023)

Obstacle induced spiral waves in a multilayered Huber-Braun (HB) neuron model - Karthikeyan Rajagopal; Janarthanan Ramadoss; Shaobo He; Prakash Duraisamy; Anitha Karthikeyan (Cognitive Neurodynamics, 2023)

Effect of coinfections on neurocognitive functioning among people with clade C HIV infection in Zambia - Lumbuka Kaunda; Mary S. Ngoma; J. Anitha Menon; Robert K. Heaton; Sara Gianella; Ajay R. Bharti; Scott Letendre; Michelli Faria de Oliveira; Knut A. Hestad (Journal of NeuroVirology, 2023)

Biosorption of methylene blue dye using a novel chitosan pectinase blend - Anitha Thulasisingh; Seenuvasan Muthulingam; Mohan Kumar; Naveenraj Rajasekar; Shantanu Mohanraj; Carlin Geor Malar (Environmental Science and Pollution Research, 2023)

Intracellular-to-extracellular localization switch of acidic lipase in Enterobacter cloacae through multi-objective medium optimization: aqueous two-phase purification and activity kinetics - Atim Asitok; Maurice Ekpenyong; Nkpa Ogarekpe; Richard Antigha; Iquo Takon; Anitha Rao; Juliet Iheanacho; Sylvester Antai (World Journal of Microbiology and Biotechnology, 2022)

Genetic mapping of drought tolerance traits phenotyped under varying drought stress environments in peanut (Arachis hypogaea L.) - Subhasini Ghosh; Supriya S. Mahadevaiah; S. Anjan Gowda; Sunil S. Gangurde; Mangesh P. Jadhav; Anil A. Hake; P. Latha; T. Anitha; V. P. Chimmad; Kiran K. Mirajkar; Vinay Sharma; Manish K. Pandey; et al. (Euphytica, 2022)

Fluorescence Variation in Selective Sensing of Hg2+and Cu2+ Ions By Coumarin-xanthene Fused Optical Probe - Mahesh Gosi; Anitha C. Kumar; Yeturu Sunandamma (Journal of Fluorescence, 2022)

Biogenic synthesis of copper nanoparticles using Vitis vinifera L. seed extract, and its in-vitro biological applications - Janakiraman Vardhana; Ramarajan Sivasankaran; Thakku R. Ramkumar; Jeyachandran Anitha (Journal of Plant Biochemistry and Biotechnology, 2022)

Ocean knowledge representation through integration of big data employing semantic web technologies - Anitha Velu; Menakadevi Thangavelu (Earth Science Informatics, 2022)

Realistic C-arm to pCT registration for vertebral localization in spine surgery - Roshan Ramakrishna Naik; Anitha H; Shyamasunder N Bhat; Nishanth Ampar; Raghuraj Kundangar (Medical & Biological Engineering & Computing, 2022)
Spine surgeries are vulnerable to wrong-level surgeries and postoperative complications because of their complex structure. Unavailability of the 3D intraoperative imaging device, low-contrast intraoperative X-ray images, variable clinical and patient conditions, manual analyses, lack of skilled technicians, and human errors increase the chances of wrong-site or wrong-level surgeries. State of the art work refers 3D-2D image registration systems and other medical image processing techniques to address the complications associated with spine surgeries. Intensity-based 3D-2D image registration systems had been widely practiced across various clinical applications. However, these frameworks are limited to specific clinical conditions such as anatomy, dimension of image correspondence, and imaging modalities. Moreover, there are certain prerequisites for these frameworks to function in clinical application, such as dataset requirement, speed of computation, requirement of high-end system configuration, limited capture range, and multiple local maxima. A simple and effective registration framework was designed with a study objective of vertebral level identification and its pose estimation from intraoperative fluoroscopic images by combining intensity-based and iterative control point (ICP)–based 3D-2D registration. A hierarchical multi-stage registration framework was designed that comprises coarse and finer registration. The coarse registration was performed in two stages, i.e., intensity similarity-based spatial localization and source-to-detector localization based on the intervertebral distance correspondence between vertebral centroids in projected and intraoperative X-ray images. Finally, to speed up target localization in the intraoperative application, based on 3D-2D vertebral centroid correspondence, a rigid ICP-based finer registration was performed. The mean projection distance error (mPDE) measurement and visual similarity between projection image at finer registration point and intraoperative X-ray image and surgeons’ feedback were held accountable for the quality assurance of the designed registration framework. The average mPDE after peak signal to noise ratio (PSNR)–based coarse registration was 20.41mm. After the coarse registration in spatial region and source to detector direction, the average mPDE reduced to 12.18mm. On finer ICP-based registration, the mean mPDE was finally reduced to 0.36 mm. The approximate mean time required for the coarse registration, finer registration, and DRR image generation at the final registration point were 10 s, 15 s, and 1.5 min, respectively. The designed registration framework can act as a supporting tool for vertebral level localization and its pose estimation in an intraoperative environment. The framework was designed with the future perspective of intraoperative target localization and its pose estimation irrespective of the target anatomy. Graphical abstract

Potential Health Risks Associated with the Heavy Metal Content in Commonly Consumed Food from Prakasam District of Andhra Pradesh, India - Arjun L. Khandare; Vakdevi Validandi; Ravi Prakash Jamalpur; Srinivas Dheeravath; Srinivasu Kurella; Anitha Chauhan; Naveen kumar Boiroju; Longvah Thingnganing (Biological Trace Element Research, 2022)

Synthesis, optimization, and characterization of biogenic manganese oxide (BioMnOx) by bacterial isolates from mangrove soils with sorbents property towards different toxic metals - Anitha Jeyaraj; Sangeetha Subramanian (BioMetals, 2022)

An Efficient Inclusion Complex Based Fluorescent Sensor for Mercury (II) and its Application in Live-Cell Imaging - Keerthana P; Hanna Abbo; Anila Rose Cherian; Salam Titinchi; Anitha Varghese (Journal of Fluorescence, 2022)

Occupational groups and its physical and mental health correlates: results from the Singapore Mental Health Study 2016 - Rajeswari Sambasivam; Anitha Jeyagurunathan; Edimansyah Abdin; Saleha Shafie; Sherilyn Chang; Janhavi Ajit Vaingankar; Siow Ann Chong; Mythily Subramaniam (International Archives of Occupational and Environmental Health, 2022)
Purpose The physical and mental wellbeing of an individual is impacted by the type occupation one does. This study aims to establish the prevalence of mental and physical disorders, the association of occupational groups and health-related quality of life, and the extent of work-loss and work-cut back in past 30 days among the employed in the Singapore resident population. Methods Data from a population-based, epidemiological survey of a representative sample of Singapore citizens and permanent residents aged 18 years and above were used. Lifetime diagnosis of select mental disorders was established using the World Health Organization’s Composite International Diagnostic Interview version 3.0 (WHO-CIDI 3.0). Data on nicotine dependence, work productivity, quality of life and socio-demographics were obtained via self-report. Ten major occupational groups based on the Singapore Standard Occupational Classification were included in the analysis. Results The sample comprised 4021 employed individuals who were predominantly males (54.7%) and aged 35–49 years (35.4%). ‘Service and sales workers’ (22.6%), ‘Professionals’ (17.3%) and ‘Legislators, senior officials and managers’ (16.4%) were the three largest occupational groups. Socio-demographic characteristics differed significantly ( p < 0.001) across all occupational groups. Lifetime prevalence of mood disorders among the employed was 8.4% and the most prevalent physical disorder was chronic pain (18.9%). No significant differences were observed in work productivity loss across the occupational groups. Conclusions The disparities in the socio-demographic characteristics and prevalence of mental and physical disorders across occupational categories provide policymakers with vital information to pilot effective interventions that can improve the psychosocial and physical conditions at work.

Seismic performance of a truss bridge with different substructure configurations - Batta Jaya Naga Satish; B. Anitha Reddy; Chava Venkatesh; Komma Hemanth Kumar Reddy; Ramamohana Reddy Bellum (Innovative Infrastructure Solutions, 2022)

First record of Cactus virus X in Dragon Fruit (Hylocereus spp.) in India - B. Parameswari; Bhaskar Bajaru; N. Sivaraj; S. K. Mangrauthia; S. Nagalakshmi; V. K. Baranwal; Prasanna Holajjer; M. Srinivas; K. Anitha (Indian Phytopathology, 2022)

The ISO 26000’s labor environmental issues during COVID-19: does corporate social responsibility help? Evidence from the Egyptian small and medium enterprises - Moustafa Mohamed Nazief Haggag Kotb Kholaif; Xiao Ming; Anitha Moosa; Kashosi Gad David (Environmental Science and Pollution Research, 2022)

Influence of salinity on the meiofaunal distribution in a hypersaline lake along the southeast coast of India - Pandiya rajan R S; Anitha Gera; Ramu K; Ranga Rao V; Ramanamurthy MV (Environmental Monitoring and Assessment, 2022)

Amorphous systems for delivery of nutraceuticals: challenges opportunities - Devendrasingh Tomar; Pankaj K. Singh; Sajidul Hoque; Sheela Modani; Anitha Sriram; Rahul Kumar; Jitender Madan; Dharmendra Khatri; Kamal Dua (Critical Reviews in Food Science and Nutrition, 2022)

Unravelling the natural dual-target inhibiting potential of cucurbit bioactive compounds for the management of cucumber mosaic virus (CMV) through computational approaches - Roshni Mohan Kumar; Ramachandra Anantapur; Anitha Peter (Journal of Proteins and Proteomics, 2021)

Nutrient dynamics and budgeting in a semi-enclosed coastal hypersaline lagoon - Akhilesh Vijay; Kumaraswami Munnooru; Gayathri Reghu; Anitha Gera; Ranga Rao Vinjamuri; Mallavarapu Venkata Ramanamurthy (Environmental Science and Pollution Research, 2021)

Hyperspectral and multispectral image fusion techniques for high resolution applications: a review - Dioline Sara; Ajay Kumar Mandava; Arun Kumar; Shiny Duela; Anitha Jude (Earth Science Informatics, 2021)

Adsorptive removal of Cd2+ ions using dolochar at an industrial-scale process optimization by response surface methodology - Utkarsh Upadhyay; Sarthak Gupta; Ankita Agarwal; Inkollu Sreedhar; Kayamkulathethu Latitha Anitha (Environmental Science and Pollution Research, 2021)

Budding Multi-matrix Technology—a Retrospective Approach, Deep Insights, and Future Perspectives - Anitha Sriram; Suma Tangirala; Srividya Atmakuri; Sajid Hoque; Sheela Modani; Saurabh Srivastava; Srushti Mahajan; Indrani Maji; Rahul Kumar; Dharmendra Khatri; Jitender Madan; Pankaj Kumar Singh (AAPS PharmSciTech, 2021)

Fluorescein Based Fluorescence Sensors for the Selective Sensing of Various Analytes - Keerthana S; Bincy Sam; Louis George; Sudhakar Y. N; Anitha Varghese (Journal of Fluorescence, 2021)

Stroke-like episodes with cerebellar ataxia as presenting manifestation of adult-onset anti-N-methyl d-aspartate receptor encephalitis: an unusual presentation - Rohan Mahale; M. K. Farsana; Anitha Mahadevan; Joydeep Mukherjee; Vathsala Lakshmi; M. Sandeep; Hansashree Padmanabha; Pooja Mailankody; Mathuranath Pavagada (Acta Neurologica Belgica, 2021)

Phenomics, genomics of oil palm (Elaeis guineensis Jacq.): way forward for making sustainable and high yielding quality oil palm - B. Kalyana Babu; R. K. Mathur; P. Anitha; G. Ravichandran; H. P. Bhagya (Physiology and Molecular Biology of Plants, 2021)

First report on the association of ‘Candidatus Phytoplasma asteris’ with lethal wilt disease of coconut (Cocos nucifera L.) in India - Merin Babu; S. Thangeswari; A. Josephrajkumar; V. Krishnakumar; A. Karthikeyan; V. Selvamani; Mol Daliya; Vinayaka Hegde; H. P. Maheswarappa; Anitha Karun (Journal of General Plant Pathology, 2021)

Genetic and genomic resources, and breeding for accelerating improvement of small millets: current status and future interventions - M. Vetriventhan; Vania C. R. Azevedo; H. D. Upadhyaya; A. Nirmalakumari; Joanna Kane-Potaka; S. Anitha; S. Antony Ceasar; M. Muthamilarasan; B. Venkatesh Bhat; K. Hariprasanna; Amasiddha Bellundagi; Deepika Cheruku; et al. (The Nucleus, 2020)
Current agricultural and food systems encourage research and development on major crops, neglecting regionally important minor crops. Small millets include a group of small- seeded cereal crops of the grass family Poaceae . This includes finger millet, foxtail millet, proso millet, barnyard millet, kodo millet, little millet, teff, fonio, job’s tears, guinea millet, and browntop millet. Small millets are an excellent choice to supplement major staple foods for crop and dietary diversity because of their diverse adaptation on marginal lands, less water requirement, lesser susceptibility to stresses, and nutritional superiority compared to major cereal staples. Growing interest among consumers about healthy diets together with climate-resilient features of small millets underline the necessity of directing more research and development towards these crops. Except for finger millet and foxtail millet, and to some extent proso millet and teff, other small millets have received minimal research attention in terms of development of genetic and genomic resources and breeding for yield enhancement. Considerable breeding efforts were made in finger millet and foxtail millet in India and China, respectively, proso millet in the United States of America, and teff in Ethiopia. So far, five genomes, namely foxtail millet, finger millet, proso millet, teff, and Japanese barnyard millet, have been sequenced, and genome of foxtail millet is the smallest (423-510 Mb) while the largest one is finger millet (1.5 Gb). Recent advances in phenotyping and genomics technologies, together with available germplasm diversity, could be utilized in small millets improvement. This review provides a comprehensive insight into the importance of small millets, the global status of their germplasm, diversity, promising germplasm resources, and breeding approaches (conventional and genomic approaches) to accelerate climate-resilient and nutrient-dense small millets for sustainable agriculture, environment, and healthy food systems.

Multi-class diagnosis of Alzheimer’s disease using cascaded three dimensional-convolutional neural network - Manu Raju; Varun P. Gopi; V. S. Anitha; Khan A. Wahid (Physical and Engineering Sciences in Medicine, 2020)

Heart malformation is an early response to valproic acid in developing zebrafish - Venugopalan Rajesh; Natarajan Deepan; Vijayakumar Anitha; Duraisamy Kalaiselvan; Subramanian Jayaseelan; Palanivel Sivakumar; Vellaiyachamy Ganesan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Identification of Potential Carbonic Anhydrase Inhibitors for Glaucoma Treatment Through an In-Silico Approach - D. Anitha; M. Suganthi; S. Gnanendra; M. Govarthanan (International Journal of Peptide Research and Therapeutics, 2020)

Methyl-CpG-binding protein 2 gene mutations and its association with epilepsy: a single centre study from the Indian subcontinent - Payal Kamdar; Maya Thomas; Sangeetha Yoganathan; Karthik Muthusamy; Beena Koshy; Samuel Philip Oommen; Rekha Aaron; Anitha Barney; Suneetha Susan C. Abraham; Sumita Danda (Journal of Genetics, 2020)

Antidiabetic, lipid lowering and antioxidant potentiating effect of Canavalia species in high fat diet-streptozotocin induced model - K. Anitha; S. Mohana Lakshmi; S. V. Satyanarayana (Advances in Traditional Medicine, 2020)

A Review of the Flora and Fauna in the Al Wathba Wetland Reserve in Abu Dhabi, United Arab Emirates - Pritpal Soorae; Sabitha Sakkir; Anitha Saji; Shahid B. Khan; Rashid Al Zaabi; Junid N. Shah; Ahmed Ali; Khaldoun Al Omari; Ahmed Al Dhaheri; Salim Javed; Sai Ravi Tubati; Shakeel Ahmed; et al. (Wetlands, 2020)

Automated segmentation of optic disc using statistical region merging and morphological operations - K. S. Nija; C. P. Anupama; Varun P. Gopi; V. S. Anitha (Physical and Engineering Sciences in Medicine, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Role of Taurine Transporter in the Retinal Uptake of Vigabatrin - Anitha Police; Vijay Kumar Shankar; S. Narasimha Murthy (AAPS PharmSciTech, 2020)

β-Sitosterol attenuates carbon tetrachloride–induced oxidative stress and chronic liver injury in rats - Ezhilarasan Devaraj; Anitha Roy; Geetha Royapuram Veeraragavan; Anitha Magesh; Aneymol Varikalam Sleeba; Lakshminarayanan Arivarasu; Brundha Marimuthu Parasuraman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The impact of northern Indian Ocean rivers on the Bay of Bengal using NEMO global ocean model - Atul Srivastava; Anitha Gera; Imran M. Momin; Ashis Kumar Mitra; Ankur Gupta (Acta Oceanologica Sinica, 2020)

Indigenous people’s response to the ban on use of forest resources in South India: a gender analysis of governmobility - Anitha Venkatesh; Kyoko Kusakabe; Veena N. (Environment, Development and Sustainability, 2020)

Tuta absoluta continues to disperse in Asia: damage, ongoing management and future challenges - Peng Han; Yunus Bayram; Liora Shaltiel-Harpaz; Fariba Sohrabi; Anitha Saji; Uulu Tair Esenali; Anvar Jalilov; Abid Ali; Pathour R. Shashank; Khasan Ismoilov; Zhao-zhi Lu; Su Wang; et al. (Journal of Pest Science, 2019)

Statistical classification of streamflow based on flow variability in west flowing rivers of Kerala, India - T. K. Drissia; V. Jothiprakash; A. B. Anitha (Theoretical and Applied Climatology, 2019)

Genetic characterization of hemagglutinin (HA) gene of influenza A viruses circulating in Southwest India during 2017 season - Anitha Jagadesh; Anjana Krishnan; Sudheesh Nair; Saritha Sivadas; Govindakarnavar Arunkumar (Virus Genes, 2019)

Medicinal metabolites with common biosynthetic pathways in Solanum nigrum - Anitha Jabamalairaj; Ryza A. Priatama; Jung Heo; Soon Ju Park (Plant Biotechnology Reports, 2019)

An Insight into Photophysical Investigation of (E)-2-Fluoro-N’-(1-(4-Nitrophenyl)Ethylidene)Benzohydrazide through Solvatochromism Approaches and Computational Studies - Ditto Abraham Thadathil; Shanu Varghese; K B Akshaya; Renjith Thomas; Anitha Varghese (Journal of Fluorescence, 2019)

Evaluation of Circulating Plasma VEGF-A, ET-1 and Magnesium Levels as the Predictive Markers for Proliferative Diabetic Retinopathy - Gopal Niranjan; A. R. Srinivasan; K. Srikanth; Gowda Pruthu; R. Reeta; Ramasamy Ramesh; Rajendiran Anitha; V. Mohana Valli (Indian Journal of Clinical Biochemistry, 2019)

Remediation of heavy metals and dyes from wastewater using cellulose-based adsorbents - Anitha George Varghese; Sherely Annie Paul; M. S. Latha (Environmental Chemistry Letters, 2019)

Change detection techniques for remote sensing applications: a survey - Anju Asokan; J. Anitha (Earth Science Informatics, 2019)

Correction to: Optimisation of a screening platform for determining IL-6 inflammatory signalling in the senescence-associated secretory phenotype (SASP) - Adam Rolt; Anitha Nair; Lynne S. Cox (Biogerontology, 2019)

Optimisation of a screening platform for determining IL-6 inflammatory signalling in the senescence-associated secretory phenotype (SASP) - Adam Rolt; Anitha Nair; Lynne S. Cox (Biogerontology, 2019)

Experimental drought reduces genetic diversity in the grassland foundation species Bouteloua eriopoda - Kenneth D. Whitney; Joann Mudge; Donald O. Natvig; Anitha Sundararajan; William T. Pockman; Jennifer Bell; Scott L. Collins; Jennifer A. Rudgers (Oecologia, 2019)

Burden of disease for workers attributable to exposure through inhalation of PPAHs in RSPM from cooking fumes - Anubha Goel; Deepshikha Ola; Anitha V. Veetil (Environmental Science and Pollution Research, 2019)

Flood Frequency Analysis Using L Moments: a Comparison between At-Site and Regional Approach - T. K. Drissia; V. Jothiprakash; A. B. Anitha (Water Resources Management, 2019)

Complex dynamics of a neuron model with discontinuous magnetic induction and exposed to external radiation - Fatemeh Parastesh; Karthikeyan Rajagopal; Anitha Karthikeyan; Ahmed Alsaedi; Tasawar Hayat; Viet-Thanh Pham (Cognitive Neurodynamics, 2018)

Leaf lipidome and transcriptome profiling of Portulaca oleracea: characterization of lysophosphatidylcholine acyltransferase - Varadarajan Venkateshwari; Anitha Vijayakumar; Arun Kumar Vijayakumar; L. Prasanna Anjaneya Reddy; Malathi Srinivasan; Ram Rajasekharan (Planta, 2018)

Aflatoxin-lysine adducts in blood serum of the Malawian rural population and aflatoxin contamination in foods (groundnuts, maize) in the corresponding areas - Anitha Seetha; Emmanuel S. Monyo; Takuji W. Tsusaka; Harry W. Msere; Frank Madinda; Tiyamika Chilunjika; Ethel Sichone; Dickson Mbughi; Benson Chilima; Limbikani Matumba (Mycotoxin Research, 2018)

Increasing incidence of tomato big bud phytoplasma in Ranga Reddy District of Telangana State, India - Madhupriya; D. Anitha Kumari; D. S. Vennila; M. Narayana Bhat; G. P. Rao (Indian Phytopathology, 2018)

Biosurfactants produced by Bacillus subtilis A1 and Pseudomonas stutzeri NA3 reduce longevity and fecundity of Anopheles stephensi and show high toxicity against young instars - Punniyakotti Parthipan; Raja Kumaresan Sarankumar; Anitha Jaganathan; Pandian Amuthavalli; Ranganathan Babujanarthanam; Pattanathu K. S. M. Rahman; Kadarkarai Murugan; Akon Higuchi; Giovanni Benelli; Aruliah Rajasekar (Environmental Science and Pollution Research, 2018)

Lost benefits and carbon uptake by protection of Indian plantations - Asbjørn Aaheim; Anton Orlov; Rajiv Kumar Chaturvedi; Priya Joshi; Anitha Sagadevan; N.H. Ravindranath (Mitigation and Adaptation Strategies for Global Change, 2018)

Assessment of groundwater quality for drinking and agricultural purposes of a few selected areas in Tamil Nadu South India: a GIS-based study - Augustine Amalraj; Anitha Pius (Sustainable Water Resources Management, 2018)

Toxic heavy metals in human blood in relation to certain food and environmental samples in Kerala, South India - Anitha Jose; Joseph George Ray (Environmental Science and Pollution Research, 2018)

Effect of gypsum on exchangeable sodium percentage and electrical conductivity in the Daeho reclaimed tidal land soil in Korea—a field scale study - Hyuck Soo Kim; Kwon-Rae Kim; Seung-Heon Lee; Anitha Kunhikrishnan; Won-Il Kim; Kye-Hoon Kim (Journal of Soils and Sediments, 2018)

Microbial Stability of Pharmaceutical and Cosmetic Products - Huy Dao; Prit Lakhani; Anitha Police; Venkataraman Kallakunta; Sankar Srinivas Ajjarapu; Kai-Wei Wu; Pranav Ponkshe; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2018)

Genetic Diversity Among Indigenous Germplasm of Brassica juncea (L.) Czern and Coss, Using Agro-Morphological and Phenological Traits - Rashmi Yadav; Ranbir Singh; Sandeep Kumar; T. V. Prasad; Rakesh Bharadwaj; Vikender Kaur; Anitha Petapadi; Ashok Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Occurrence of aflatoxins and its management in diverse cropping systems of central Tanzania - Anitha Seetha; Wills Munthali; Harry W. Msere; Elirehema Swai; Yasinta Muzanila; Ethel Sichone; Takuji W. Tsusaka; Abhishek Rathore; Patrick Okori (Mycotoxin Research, 2017)

Study on Photophysical Properties of N-Arylphthalamic Acid Derivative Containing 1, 2, 4-Triazole Scaffold - K. B. Akshaya; Anitha Varghese; Y. N. Sudhakar; Prajwal Lourdes Lobo; Louis George (Journal of Fluorescence, 2017)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

Chitosan-fabricated Ag nanoparticles and larvivorous fishes: a novel route to control the coastal malaria vector Anopheles sundaicus? - Kadarkarai Murugan; Jaganathan Anitha; Udaiyan Suresh; Rajapandian Rajaganesh; Chellasamy Panneerselvam; Al Thabiani Aziz; Li-Chun Tseng; Kandasamy Kalimuthu; Mohamad Saleh Alsalhi; Sandhanasamy Devanesan; Marcello Nicoletti; Santosh Kumar Sarkar; et al. (Hydrobiologia, 2017)

Molecular characterization of neuraminidase genes of influenza A(H3N2) viruses circulating in Southwest India from 2009 to 2013 - Anitha Jagadesh; Abdul Ajees Abdul Salam; Vahid Rajabali Zadeh; Anjana Krishnan; Govindakarnavar Arunkumar (Archives of Virology, 2017)

The Neuropeptide Orexin-A Inhibits the GABAA Receptor by PKC and Ca2+/CaMKII-Dependent Phosphorylation of Its β1 Subunit - Divya Sachidanandan; Haritha P. Reddy; Anitha Mani; Geoffrey J. Hyde; Amal Kanti Bera (Journal of Molecular Neuroscience, 2017)

In vitro antioxidant, antimicrobial, cytotoxic potential of gold and silver nanoparticles prepared using Embelia ribes - Manikandan Dhayalan; Michael Immanuel Jesse Denison; Anitha Jegadeeshwari L; Kathiravan Krishnan; Nagendra Gandhi N (Natural Product Research, 2017)

Estimation of Ground-State and Singlet Excited-State Dipole Moments of Substituted Schiff Bases Containing Oxazolidin-2-one Moiety through Solvatochromic Methods - Rekha Kumari; Anitha Varghese; Louis George (Journal of Fluorescence, 2017)

A Preliminary Report on the Butterfly Diversity of Kurumpuram Reserve Forest, Marakkanam, Tamil Nadu - K. Silambarasan; K. Sujatha; A. Anitha Joice; P. Senthilkumaar; E. Rajalakshmi (Proceedings of the Zoological Society, 2016)

Effect of oral supplementation with polyamines on testicular development and egg production in Bombyx mori (Lepidoptera: Bombycidae) - Danti Kumari Mysarla; Aparna Yerra; Prasanthi Siripurapu; Anitha Mamillapalli (Applied Entomology and Zoology, 2016)

Influenza virus neuraminidase (NA): a target for antivirals and vaccines - Anitha Jagadesh; Abdul Ajees Abdul Salam; Piya Paul Mudgal; Govindakarnavar Arunkumar (Archives of Virology, 2016)

Evidence for the significant role of sea surface temperature distributions over remote tropical oceans in tropical cyclone intensity - Anitha Kumari Hegde; Ryuichi Kawamura; Tetsuya Kawano (Climate Dynamics, 2016)

De novo assembly and characterization of global transcriptome of coconut palm (Cocos nucifera L.) embryogenic calli using Illumina paired-end sequencing - M. K. Rajesh; T. P. Fayas; S. Naganeeswaran; K. E. Rachana; U. Bhavyashree; K. K. Sajini; Anitha Karun (Protoplasma, 2016)

Exploiting the antivirulence efficacy of an ajoene-ciprofloxacin combination against Pseudomonas aeruginosa biofilm associated murine acute pyelonephritis - Anitha Vadekeetil; Hina Saini; Sanjay Chhibber; Kusum Harjai (Biofouling, 2016)

Co-composting solid biowastes with alkaline materials to enhance carbon stabilization and revegetation potential - Saikat Chowdhury; Nanthi S. Bolan; Balaji Seshadri; Anitha Kunhikrishnan; Hasintha Wijesekara; Yilu Xu; Jianjun Yang; Geon-Ha Kim; Donald Sparks; Cornelia Rumpel (Environmental Science and Pollution Research, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

A New Fluorescent Sensor Based on Bisindolizine Derivative - Anitha I; Sheela Gopal M; Divya Thomas (Journal of Fluorescence, 2016)

Agronomic improvements can make future cereal systems in South Asia far more productive and result in a lower environmental footprint - Jagdish Kumar Ladha; Adusumilli Narayana Rao; Anitha K. Raman; Agnes Tirol Padre; Achim Dobermann; Mahesh Gathala; Virender Kumar; Yashpal Saharawat; Sheetal Sharma; Hans Peter Piepho; Md Mursedul Alam; Ranjan Liak; et al. (Global Change Biology, 2016)
South Asian countries will have to double their food production by 2050 while using resources more efficiently and minimizing environmental problems. Transformative management approaches and technology solutions will be required in the major grain‐producing areas that provide the basis for future food and nutrition security. This study was conducted in four locations representing major food production systems of densely populated regions of South Asia. Novel production‐scale research platforms were established to assess and optimize three futuristic cropping systems and management scenarios (S2, S3, S4) in comparison with current management (S1). With best agronomic management practices ( BMP s), including conservation agriculture ( CA ) and cropping system diversification, the productivity of rice‐ and wheat‐based cropping systems of South Asia increased substantially, whereas the global warming potential intensity (GWPi) decreased. Positive economic returns and less use of water, labor, nitrogen, and fossil fuel energy per unit food produced were achieved. In comparison with S1, S4, in which BMP s, CA and crop diversification were implemented in the most integrated manner, achieved 54% higher grain energy yield with a 104% increase in economic returns, 35% lower total water input, and a 43% lower GWPi. Conservation agriculture practices were most suitable for intensifying as well as diversifying wheat–rice rotations, but less so for rice–rice systems. This finding also highlights the need for characterizing areas suitable for CA and subsequent technology targeting. A comprehensive baseline dataset generated in this study will allow the prediction of extending benefits to a larger scale.

Sulfur crosslinks from thermal degradation of chitosan dithiocarbamate derivatives and thermodynamic study for sorption of copper and cadmium from aqueous system - Soon Kong Yong; William M. Skinner; Nanthi S. Bolan; Enzo Lombi; Anitha Kunhikrishnan; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

Mammogram segmentation using maximal cell strength updation in cellular automata - J. Anitha; J. Dinesh Peter (Medical & Biological Engineering & Computing, 2015)

Non-timber forest products certification and management: a socioeconomic study among the Kadars in Kerala, India - Jyotsna Krishnakumar; John F. Yanagida; V. Anitha; Rajeev Balakrishnan; Theodore J. K. Radovich (Environment, Development and Sustainability, 2015)

Bioavailability and ecotoxicity of arsenic species in solution culture and soil system: implications to remediation - Nanthi Bolan; Santiago Mahimairaja; Anitha Kunhikrishnan; Balaji Seshadri; Ramya Thangarajan (Environmental Science and Pollution Research, 2015)

Concomitant reduction and immobilization of chromium in relation to its bioavailability in soils - Girish Choppala; Nanthi Bolan; Anitha Kunhikrishnan; William Skinner; Balaji Seshadri (Environmental Science and Pollution Research, 2015)

The multiple associations of Klippel–Feil syndrome - Anitha Jasper; Sniya Valsa Sudhakar; Gibikote V. Sridhar (Acta Neurologica Belgica, 2015)

Applications of thin-layer chromatography in extraction and characterisation of ajoene from garlic bulbs - Anitha Vadekeetil; Gurpreet Kaur; Sanjay Chhibber; Kusum Harjai (Natural Product Research, 2015)

Variability of sea surface salinity in the tropical Indian Ocean as inferred from Aquarius and in situ data sets - Imranali M. Momin; Ashis K. Mitra; Satya Prakash; D.K. Mahapatra; Anitha Gera; E.N. Rajagopal (International Journal of Remote Sensing, 2015)

Gene and Protein Network Analysis of AmpC β Lactamase - P. Anitha; Susmita Bag; Anand Anbarasu; Sudha Ramaiah (Cell Biochemistry and Biophysics, 2015)

Evaluation of Serum Vitamin B12 Levels and Its Correlation with Anti-Thyroperoxidase Antibody in Patients with Autoimmune Thyroid Disorders - S. Jaya Kumari; Ganapathy Bantwal; Anitha Devanath; Vageesh Aiyyar; Madhuri Patil (Indian Journal of Clinical Biochemistry, 2015)

Sources, Distribution, Environmental Fate, and Ecological Effects of Nanomaterials in Wastewater Streams - Anitha Kunhikrishnan; Ho Kyong Shon; Nanthi S. Bolan; Ibrahim El Saliby; Saravanamuthu Vigneswaran (Critical Reviews in Environmental Science and Technology, 2015)

Synthesis and characterization of novel chalcone linked imidazolones as potential antimicrobial and antioxidant agents - Anitha Sadula; Usha Rani Peddaboina; Prameela Subhashini N. J (Medicinal Chemistry Research, 2015)

Coastal vulnerability assessment: a case study on erosion and coastal change along Tuticorin, Gulf of Mannar - Anitha Parthasarathy; Usha Natesan (Natural Hazards, 2015)

Standalone EST microsatellite mining and analysis tool (SEMAT): for automated EST-SSR analysis in plants - Naganeeswaran Sudalaimuthu Asari; Manimekalai Ramaswamy; Elain Apshara Subbian; Manju Kalathil Palliyarakkal; S. K. Malhotra; Anitha Karun (Tree Genetics & Genomes, 2014)

Simultaneous detection of groundnut rosette assistor virus (GRAV), groundnut rosette virus (GRV) and satellite RNA (satRNA) in groundnuts using multiplex RT-PCR - S. Anitha; E. S. Monyo; P. Okori (Archives of Virology, 2014)

Molecular characterization of Indian isolate of peanut mottle virus and immunodiagnosis using bacterial expressed core capsid protein - K. Soumya; M. Yogita; Y. Prasanthi; K. Anitha; P. B. Kavi Kishor; R. K. Jain; Bikash Mandal (VirusDisease, 2014)

Effect of industrial waste products on phosphorus mobilisation and biomass production in abattoir wastewater irrigated soil - Balaji Seshadri; Anitha Kunhikrishnan; Nanthi Bolan; Ravi Naidu (Environmental Science and Pollution Research, 2014)

MARSpline model for lead seven-day maximum and minimum air temperature prediction in Chennai, India - K Ramesh; R Anitha (Journal of Earth System Science, 2014)

Identification and molecular mapping of two soybean aphid resistance genes in soybean PI 587732 - Ki-Seung Kim; Anitha Chirumamilla; Curtis B. Hill; Glen L. Hartman; Brian W. Diers (Theoretical and Applied Genetics, 2014)

Coregulation of host–response genes in integument: switchover of gene expression correlation pattern and impaired immune responses induced by dipteran parasite infection in the silkworm, Bombyx mori - Anitha Jayaram; Appukuttan Nair R. Pradeep; Arvind K. Awasthi; Geetha N. Murthy; Kangayam M. Ponnuvel; Sirigineedi Sasibhushan; Guruprasad C. Rao (Journal of Applied Genetics, 2014)

Shallow geological environment of Krishna–Godavari offshore, eastern continental margin of India as inferred from the interpretation of high resolution sparker data - G ANITHA; M V RAMANA; T RAMPRASAD; P DEWANGAN; M ANURADHA (Journal of Earth System Science, 2014)

Effect of Coal Combustion Products in Reducing Soluble Phosphorus in Soil II: Leaching Study - Balaji Seshadri; Nanthi S. Bolan; Anitha Kunhikrishnan; Girish Choppala; Ravi Naidu (Water, Air, & Soil Pollution, 2014)

Scope of novel and rare bulbiferous coconut palms (Cocos nucifera L.) - B. A. Jerard; M. K. Rajesh; S. A. Elain; K. K. Sajini; Shafeeq Rahman; T. P. Fayas; Anitha Karun (Genetic Resources and Crop Evolution, 2014)

A Study to Evaluate Lipid Profile in Treatment Naïve HIV Positive Patients - Anitha Devanath; Somdattaa Ray; Ravi Kumar; B. S. Prarthana (Indian Journal of Clinical Biochemistry, 2014)

Potential of Novel Bacterial Consortium for the Remediation of Chromium Contamination - Periyasamy Panneerselvam; Girish Choppala; Anitha Kunhikrishnan; Nanthi Bolan (Water, Air, & Soil Pollution, 2013)

Comparative Sorption and Mobility of Cr(III) and Cr(VI) Species in a Range of Soils: Implications to Bioavailability - Girish Choppala; Nanthi Bolan; Dane Lamb; Anitha Kunhikrishnan (Water, Air, & Soil Pollution, 2013)

Plantlet regeneration through indirect shoot organogenesis and somatic embryogenesis in Justicia gendarussa Burm. f., a medicinal plant - N. Bhagya; K. R. Chandrashekar; Anitha Karun; U. Bhavyashree (Journal of Plant Biochemistry and Biotechnology, 2013)

Effect of Aspect Ratio on the Monotonic Shear Behaviour: Micromechanical Interpretations - S. D. Anitha Kumari; T. G. Sitharam (Geotechnical and Geological Engineering, 2013)

Mathematical Modeling of a Carrier-Mediated Transport Process in a Liquid Membrane - Subramanian Ganesan; Shanmugarajan Anitha; Alwarappan Subbiah; Lakshmanan Rajendran (The Journal of Membrane Biology, 2013)

Rhizoreduction of arsenate and chromate in Australian native grass, shrub and tree vegetation - Nanthi Bolan; Anitha Kunhikrishnan; Joan Gibbs (Plant and Soil, 2013)

Antihypercholesterolemic and antioxidative effects of an extract of the oyster mushroom, Pleurotus ostreatus, and its major constituent, chrysin, in Triton WR-1339-induced hypercholesterolemic rats - Ramalingam Anandhi; Thangaraj Annadurai; Thirugnanasambandhar S. Anitha; Arumugam R. Muralidharan; Kalifulla Najmunnisha; Vasanthi Nachiappan; Philip A. Thomas; Pitchairaj Geraldine (Journal of Physiology and Biochemistry, 2013)

Activation of autophagic programmed cell death and innate immune gene expression reveals immuno-competence of integumental epithelium in Bombyx mori infected by a dipteran parasitoid - Appukuttan Nair R. Pradeep; Jayaram Anitha; Arvind K. Awasthi; Mohd. A. Babu; Murthy N. Geetha; Hariharan K. Arun; Sagar Chandrashekhar; Guruprasad C. Rao; Nanjappa B. Vijayaprakash (Cell and Tissue Research, 2013)

Effect of Clean Coal Combustion Products in Reducing Soluble Phosphorus in Soil I. Adsorption Study - Balaji Seshadri; Nanthi S. Bolan; Anitha Kunhikrishnan (Water, Air, & Soil Pollution, 2013)

Comparative Study on Precipitation Techniques for Protease Isolation and Purification from Labeo rohita Viscera - S. Geethanjali; Anitha Subash (Journal of Aquatic Food Product Technology, 2013)

Evaluation of groundwater quality in and around Peenya industrial area of Bangalore, South India using GIS techniques - Anitha Pius; Charmaine Jerome; Nagaraja Sharma (Environmental Monitoring and Assessment, 2012)

Pollen morphology of the three subgenera of Alnus - Estella B. Leopold; Joshua Birkebak; Linda Reinink-Smith; Anitha P. Jayachandar; Paula Narváez; Stephanie Zaborac-Reed (Palynology, 2012)

Phytoavailability of copper in the presence of recycled water sources - Anitha Kunhikrishnan; Nanthi Sirangie Bolan; Ravi Naidu (Plant and Soil, 2011)

Prevention of Selenite-Induced Cataractogenesis by an Ethanolic Extract of Cineraria maritima: An Experimental Evaluation of the Traditional Eye Medication - Thirugnanasambandhar Sivasubramania Anitha; Thangaraj Annadurai; Philip A. Thomas; Pitchairaj Geraldine (Biological Trace Element Research, 2011)

Erratum to: Mitochondrial and nuclear gene mutations in the type 2 diabetes patients of Coimbatore population - Viswanadha Vijaya Padma; Shobana Anitha; Elango Santhini; Duraisamy Pradeepa; Dominic Tresa; Perumal Ganesan; Periyasamy Ishwarya; Ramanathan Balamurugan (Molecular and Cellular Biochemistry, 2011)

A macroeconomic analysis of adaptation to climate change impacts on forests in India - Asbjørn Aaheim; Ranjith Gopalakrishnan; Rajiv Kumar Chaturvedi; N. H. Ravindranath; Anitha D. Sagadevan; Nitasha Sharma; Taoyuan Wei (Mitigation and Adaptation Strategies for Global Change, 2011)

Integrated modelling approaches to analysis of climate change impacts on forests and forest management - Asbjørn Aaheim; Rajiv Kumar Chaturvedi; Anitha A. Sagadevan (Mitigation and Adaptation Strategies for Global Change, 2011)

Mitochondrial and nuclear gene mutations in the type 2 diabetes patients of Coimbatore population - Viswanadha Vijaya Padma; Shobana Anitha; Elango Santhini; Duraisamy Pradeepa; Dominic Tresa; Perumal Ganesan; Periyasamy Ishwarya; Ramanathan Balakrishnan (Molecular and Cellular Biochemistry, 2010)

The potential impacts of sea level rise along the coastal zone of Kanyakumari District in Tamilnadu, India - Usha Natesan; Anitha Parthasarathy (Journal of Coastal Conservation, 2010)

Estimation of atmospheric surface layer parameters and numerical simulation using MM5 at Mangalore, West Coast of India - Anitha Kumari Hegde; R. Venkatesan; C. V. Srinivas; K. M. Balakrishna (Meteorology and Atmospheric Physics, 2010)

Methodology to map the spread of an invasive plant ( Lantana camara L. ) in forest ecosystems using Indian remote sensing satellite data - M. M. Kimothi; Anitha Dasari (International Journal of Remote Sensing, 2010)

Liposome Damage and Modeling of Fragments of Human Islet Amyloid Polypeptide (IAPP) Support a Two-Step Model of Membrane Destruction - Deborah L. Heyl; Joshua M. Osborne; Sarika Pamarthy; Shyamprasad Samisetti; Andrew W. Gray; Anitha Jayaprakash; Srikanth Konda; Dorothy J. Brown; Samuel R. Miller; Reza Eizadkhah; Maria C. Milletti (International Journal of Peptide Research and Therapeutics, 2010)

Usefulness of lipase / amylase ratio in acute pancreatitis in South Indian population - Anitha Devanath; Jaya Kumari; Jim Joe; Saly Peter; Sugirtha Rajan; Laly Sabu; Shivshankar; Janet Mary; Smitha; Roselin; Arokiasami (Indian Journal of Clinical Biochemistry, 2009)

Space-time structures of earthquakes - T. N. Krishnamurti; Ruby Krishnamurti; Anitha D. Sagadevan; Arindam Chakraborty; William K. Dewar; Carol Anne Clayson; James F. Tull (Meteorology and Atmospheric Physics, 2009)

Changes in structural attributes of plant communities along disturbance gradients in a dry deciduous forest of Western Ghats, India - K. Anitha; Shijo Joseph; E. V. Ramasamy; S. Narendra Prasad (Environmental Monitoring and Assessment, 2009)

Effect of auxins on adventitious rooting from stem cuttings of candidate plus tree Pongamia pinnata (L.), a potential biodiesel plant - Vigya Kesari; Anitha Krishnamachari; Latha Rangan (Trees, 2009)

Cardiac dysrhythmia produced by Mesobuthus tamulus venom involves NO-dependent G-Cyclase signaling pathway - Sadhana Kanoo; Maloy B. Mandal; Anitha B. Alex; Shripad B. Deshpande (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Analysis of diversity and distribution of Jatropha curcas L. germplasm using Geographic Information System (DIVA-GIS) - N. Sunil; N. Sivaraj; K. Anitha; Babu Abraham; Vinod Kumar; E. Sudhir; M. Vanaja; K. S. Varaprasad (Genetic Resources and Crop Evolution, 2009)

Hypermagnesemia in diabetic end stage renal disease (ESRD) patients - K N Shashidhar; Mamatha Kunder; K Anitha Shenoy; A Hemalatha; AVM Kutty; HV Shetty (Indian Journal of Clinical Biochemistry, 2007)

Transition Metal-Mediated Liposomal Encapsulation of Irinotecan (CPT-11) Stabilizes the Drug in the Therapeutically Active Lactone Conformation - Euan Ramsay; Jehan Alnajim; Malathi Anantha; Aman Taggar; Anitha Thomas; Katarina Edwards; Göran Karlsson; Murray Webb; Marcel Bally (Pharmaceutical Research, 2006)

Association analysis of SOD2 variants with methamphetamine psychosis in Japanese and Taiwanese populations - Kazuhiko Nakamura; Chih-Ken Chen; Yoshimoto Sekine; Yasuhide Iwata; A. Anitha; El-Wui Loh; Nori Takei; Atsuko Suzuki; Masayoshi Kawai; Kiyokazu Takebayashi; Katsuaki Suzuki; Yoshio Minabe; et al. (Human Genetics, 2006)

Influence of age and gender on the jaw-stretch and blink reflexes - Anitha Peddireddy; Kelun Wang; Peter Svensson; Lars Arendt-Nielsen (Experimental Brain Research, 2006)

Application of Isozyme Data in Fingerprinting Napier Grass (Pennisetum purpureum Schum.) for Germplasm Management - Anitha P. Bhandari; D. H. Sukanya; C. R. Ramesh (Genetic Resources and Crop Evolution, 2006)

CandiVF – Candida albicans Virulence Factor Database - Songsak Tongchusak; Sansanee C. Chaiyaroj; Anitha Veeramani; Judice L. Y. Koh; Vladimir Brusic (International Journal of Peptide Research and Therapeutics, 2005)

Arterial blood gas management during cardiopulmonary bypass - O. P. Sanjay; Anitha Devnath; B. C. Thejas (Indian Journal of Clinical Biochemistry, 2005)

Response surface methodology for optimization and characterization of limonene-based coenzyme Q10 self-nanoemulsified capsule dosage form - Anitha Palamakula; Mohammad T. H. Nutan; Mansoor A. Khan (AAPS PharmSciTech, 2004)

Lipoic acid attenuates hypertension and improves insulin sensitivity, kallikrein activity and nitrite levels in high fructose-fed rats - V. Thirunavukkarasu; A. T. Anitha Nandhini; C. V. Anuradha (Journal of Comparative Physiology B, 2004)

Glutathione S-transferase M1 and T1 null genotype distribution in South Indians - A.T. Naveen; C. Adithan; N. Padmaja; C.H. Shashindran; B.K. Abraham; K. Satyanarayanamoorthy; P. Anitha; N. Gerard; R. Krishnamoorthy (European Journal of Clinical Pharmacology, 2004)

Estimation of reference values in liver function test in health plan individuals of an urban south Indian population - Sultana Furruqh; D. Anitha; T. Venkatesh (Indian Journal of Clinical Biochemistry, 2004)

Circadian clocks and life-history related traits: Is pupation height affected by circadian organization inDrosophila melanogaster? - Dhanashree A. Paranjpe; D. Anitha; Vijay Kumar Sharma; Amitabh Joshi (Journal of Genetics, 2004)

Identification of Virulent Isolates of the Entomopathogenic Fungus Nomuraea Rileyi (F) Samson for the Management of Helicoverpa Armigera and Spodoptera Litura - P.S. Vimala Devi; Y.G. Prasad; D. Anitha Chowdary; L. Mallikarjuna Rao; K. Balakrishnan (Mycopathologia, 2003)

Membrane associated estrogen receptors and related proteins: Localization at the plasma membrane and the endoplasmic reticulum - Anitha P. Govind; Raghava Varman Thampan (Molecular and Cellular Biochemistry, 2003)

Plant regeneration from embryo-derived callus of oil palm – the effect of exogenous polyamines - M.K. Rajesh; E. Radha; Anitha Karun; V.A. Parthasarathy (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Identification of the Sex Pheromone of Holotrichia reynaudi - Andrew Ward; Chris Moore; V. Anitha; John Wightman; D. John Rogers (Journal of Chemical Ecology, 2002)

Cost-effective multiplication of the entomopathogenic fungus Nomuraea rileyi (F) Samson - P.S. Vimala Devi; Anitha Chowdary; Y.G. Prasad (Mycopathologia, 2001)

The changing scenario in diagnosing prostate cancer - D. Anitha; T. Venkatesh (Indian Journal of Clinical Biochemistry, 2000)

Immunological characterization of spore proteins of the microsporidian Nosema bombycis - T. Anitha Sironmani (World Journal of Microbiology and Biotechnology, 1999)